Anti‐inflammatory/regulatory cytokine microenvironment mediated by IL‐4 and IL‐10 coordinates the immune response in hemophilia A patients infected chronically with Hepatitis C virus1. Issue 6 (16th April 2013) - Pimentel, João Paulo; Chaves, Daniel Gonçalves; Araújo, Ana Ruth Silva; de Araújo, Erbênia Maria Martins; da Silva Fraporti, Liziara; Neves, Walter Luiz Lima; Tarragô, Andrea Monteiro; Torres, Katia Luz; Gentz, Solange Henschke Lima; Teixeira‐Carvalho, Andréa; Martins‐Filho, Olindo Assis; Malheiro, Adriana
Abstract: In the past decades patients with hemophilia were infected commonly by hepatitis C virus (HCV) and a significant number of patients are infected chronically. Focusing on the role of the immune system for controlling and or maintaining HCV infection, the leukocyte and cytokine profiles of peripheral blood from hemophilia A patients and other patients with and without HCV infection were studied. The results demonstrated that hemophilia A is characterized by a general state of circulating leukocytes activation along with an overall increase in the frequency of IL‐6 and IL‐10 with decrease of IL‐8 and IL‐12. HCV infection of patients with hemophilia A does not influence further the activation state of circulating leukocytes but is accompanied by lower levels of alanine transaminase (ALT) and a prominent anti‐inflammatory/regulatory serum cytokine pattern, mediated by IL‐4 and IL‐10. Additionally, the results demonstrated that hemophilia A patients infected with HCV displaying No/Low antibody response to C33c and C22 have significant lower viral load and higher serum levels of IL‐12 and IL‐4. This finding suggests that the differential RIBA reactivity to C33c/C22 HCV core proteins may have a putative value as a prognostic biomarker for the infection in hemophilia A patients. J. Med. Virol. 85: 1009–1018, 2013. © 2013 Wiley Periodicals, Inc.